2018
DOI: 10.2134/jeq2018.04.0154
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Wetland Mitigation: Can Rice Fields Remediate Pesticides in Agricultural Runoff?

Abstract: Pesticides are responsible for nearly 1900 water quality impairments in the United States. Impacts of pesticide runoff on aquatic ecosystems can be mitigated by implementing management practices such as constructed wetlands, grass buffers, and vegetated ditches. A new practice currently being examined is the use of rice (Oryza sativa L.) fields for phytoremediation of pesticide‐contaminated water. Rice is cultivated on every continent except Antarctica and is the staple food crop of 20% of the world's populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The primary studies that showed high removal efficiencies (greater than 75%) were larger for mesocosm studies. Of the studies that analyzed the mesocosm scale, 68% had at least one contaminant removed at an efficiency greater than or equal to 75% [16,23,45 160,173,174,184,186,187,189,191,196,206,208,212]. However, efficiencies between studies for specific contaminants and/or classes were not able to undergo statistical evaluation due to few studies having the same contaminant and/or class evaluated.…”
Section: Scale and Type Of Wetlands Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary studies that showed high removal efficiencies (greater than 75%) were larger for mesocosm studies. Of the studies that analyzed the mesocosm scale, 68% had at least one contaminant removed at an efficiency greater than or equal to 75% [16,23,45 160,173,174,184,186,187,189,191,196,206,208,212]. However, efficiencies between studies for specific contaminants and/or classes were not able to undergo statistical evaluation due to few studies having the same contaminant and/or class evaluated.…”
Section: Scale and Type Of Wetlands Usedmentioning
confidence: 99%
“…The least studied systems were depressions, ephemeral wetlands, wetland buffers, recirculating constructed wetlands, and salt marshes each appearing only once throughout the primary studies. However, six studies investigated the ability of rice fields to mitigate nutrients, pesticides, and antibiotics as a wetland system in Mississippi, U.S. [63,160,174], India [56], China [115], and Spain [103] with high removal efficiencies (58-100%) for several different contaminants (e.g., diazinon, benthocarb, carbofuran, atrazine, permethrin, NH 4 + -N, NO 3 -N, nitrate-N).…”
Section: Scale and Type Of Wetlands Usedmentioning
confidence: 99%
“…Herbicides account for about 62% of total pesticides usage in agriculture in the United States, and the five most used herbicides during the past two decades were glyphosate, atrazine, metolachlor-( S ), 2,4-D, and acetochlor . As one of the most frequently detected pesticides, the concentration of atrazine in surface water in the Midwest and South of the US reached 53 μg/L in 2018 . Very few pesticides are completely mineralized after biotic or abiotic degradation.…”
Section: Introductionmentioning
confidence: 99%
“…18 As one of the most frequently detected pesticides, the concentration of atrazine in surface water in the Midwest and South of the US reached 53 μg/L in 2018. 19 Very few pesticides are completely mineralized after biotic or abiotic degradation. Some of their degradation intermediates, which possess even higher toxicity, have been detected at higher concentrations in drinking water and surface water compared to their parent forms.…”
Section: Introductionmentioning
confidence: 99%
“…VTSs studied in literature include very different types of systems (Lange et al, 2011), including vegetated ditches or detention ponds with hydraulic retention times (HRT) ranging in the order of minutes to several hours (Bundschuh et al, 2016;Elsaesser et al, 2011) or constructed wetlands in which HRT may reach several weeks, when operated in batch mode (Tournebize et al, 2017;Maillard et al, 2016). Pesticide mitigation has also been observed in other systems in which water is temporally stored such as barrage fish ponds (Gaillard et al, 2016) or rice fields (Moore et al, 2018). While contaminant mass loss (RM) is mainly observed in systems with longer HRT, systems with short HRT have been shown to efficiently reduce peak concentration (RC) and the associated acute toxicity (Bundschuh et al, 2016;Elsaesser et al, 2011;Stehle et al, 2011).…”
Section: Introductionmentioning
confidence: 99%